Mediating innovation through language teacher education - East, Martin ca. 20./21. Jh (Cambridge University Press, 2022)
This Element examines how pedagogical innovation in language classrooms can be mediated through language teacher education (LTE) by subjecting the author's own practices as a teacher educator to scrutiny. Starting from the premise that implementing innovation can be a challenging enterprise, effective LTE is framed as being built on helping practitioners to recognise and confront often deeply-rooted beliefs and adjust subsequent practices through critical reflection on what an innovation may look like both theoretically and practically. A critically reflective lens is then applied to the author's own work as a teacher educator over several years through a research approach known as self-study of teacher education practices or S-STEP. The approach highlights changes to the author's beliefs and practices as lessons emerged from beginning teachers' engagement with innovative ideas. These are presented with the aim of better understanding how teachers' beliefs and practices with regard to innovation can be enhanced effectively
Title from publisher's bibliographic system (viewed on 31 Oct 2022)
Keywords: Language teachers / Training of; Lehrerbildung; Handlungsorientierter Unterricht; Selbstreflexion; Fremdsprachenunterricht; Innovation